2017
DOI: 10.4102/sajbm.v48i1.17
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility reporting by South African mining companies: Evidence of legitimacy theory

Abstract: This paper offers evidence on the relevance of legitimacy theory for explaining changes in the frequency of corporate social responsibility (CSR) disclosures by South African platinum mining companies following violent strike action during 2012 at Marikana. The results show that all of the South African platinum mining companies provide additional information dealing specifically with the strike taking place at Marikana. This is more pronounced for the company directly involved in the incident. The research al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 48 publications
1
25
0
3
Order By: Relevance
“…Legitimacy theory has been used to support various research in order to support the reasons that motivate companies to invest in social and environmental disclosure without any legal force. In this perspective, Dube and Maroun () investigated the relevance of the legitimacy theory to explain the changes in the frequency of corporate social responsibility (CSR) disclosures by South African platinum mining companies following a violent strike in Marikana in 2012. The results showed that all the platinum mining companies in South Africa provide additional information specifically related to the strike that occurred in Marikana thus confirming the assumptions of the theory of legitimacy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Legitimacy theory has been used to support various research in order to support the reasons that motivate companies to invest in social and environmental disclosure without any legal force. In this perspective, Dube and Maroun () investigated the relevance of the legitimacy theory to explain the changes in the frequency of corporate social responsibility (CSR) disclosures by South African platinum mining companies following a violent strike in Marikana in 2012. The results showed that all the platinum mining companies in South Africa provide additional information specifically related to the strike that occurred in Marikana thus confirming the assumptions of the theory of legitimacy.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Parallels for this are abundant in the global context. However, it is noteworthy that researchers studying CSR disclosure in Bangladesh have used theoretical frameworks only to explain their findings, but not to develop their models, which stands in sharp contrast to some studies in the developed context (Aerts, 2014;Simmons, 2013;Dube & Maroun, 2017). This is, perhaps, a limiting approach, which attests to the under-theorization of CSR in Bangladesh.…”
Section: Discussion and Research Gapsmentioning
confidence: 99%
“…Emphasis on child labor, for instance, was salient in the 1990s and re-emerged in 2010both time periods characterized by strong negative publicity worldwide regarding child labor. Much in line with this, there is an abundance of literature in the global context, which documents a rise in CSR reporting following critical social events (O' Donnovan, 2002;Dube & Maroun, 2017). Dube and Maroun (2017) document a rise in disclosure in the South African mining industry following a series of violent worker strikes.…”
Section: Theoretical Perspectives Used To Explain Csr Reporting Practmentioning
confidence: 97%
“…The mining sector in South Africa is politically sensitive due to very active labour unions and high labour unrest. Dube and Maroun (2017) found that platinum mining companies in South Africa changed their CSR disclosures in response to the fatal protests at the Marikana platinum mine. Looking at IR communications in South Africa, two recent studies investigated the quality of JSE-listed companies' online IR practices.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%